On an undocumented type of predicate ellipsis in Spanish and its consequences for the theory of ellipsis licensing - Saab, Andrés Leandro (2023)
In this paper, we introduce and discuss a type of ellipsis in Spanish, undocumented in the previous literature, which we will refer to as Predicate Phrase Ellipsis (PredP-Ellipsis), and its consequences for the theory of ellipsis licensing. PredP-Ellipsis is a type of ellipsis in which the complement of a copular verb undergoes deletion, whenever there is contrastive focus (typically encoded in Polarity) involved in the sentence. We provide an account for why this type of ellipsis is allowed in a language that lacks lower ellipses in the verbal domain (such as vP-Ellipsis), and implement our proposal by introducing an [E]-feature which is typically licensed when it enters into an Agree relation with a Polarity head higher in the structure.